73 Effects of dietary neutral detergent fiber and standardized ileal digestible lysine levels on growth performance and carcass characteristics of growing-finishing pigs. (30th November 2020) - Orlando, Uislei; Lu, Ning; Vier, Carine; Cast, Wayne; Zhou, Xun; Young, Malachy
Abstract: Our objective was to determine the effects of feeding different neutral detergent fiber (NDF) and standardized ileal digestible (SID) lysine (Lys) levels on performance of growing-finishing pigs from 30- to 130-kg. A total of 2, 016 barrows and gilts (PIC 280×Camborough, initial BW of 29.6±0.53 kg) were allotted to a randomized complete block design with a 2×2 factorial arrangement. Dietary treatments (Table 1) consisted with two NDF levels (13% or 20%) and two SID Lys curves (PIC2008 or PIC2016). There were 21 mixed-sex pigs per pen, and 24 pens per treatment. The experiment diets were fed in 3 phases. Wheat, wheat by-products, peas, and canola oil were used with NRC (2012) loading values to achieve treatments, and all diets were formulated to be iso-caloric (2, 420 kcal NE/kg). Experimental data were analyzed using generalized linear mixed models with pen as the experimental unit. Increasing NDF level resulted in a reduction (P< 0.05) in average daily gain (ADG), average daily feed intake, hot carcass weight, carcass yield, carcass ADG, and backfat depth (Table 2), and tended to decrease percentage of removals and mortality (P=0.10). Pigs fed PIC2016 Lys curve had greater ADG and carcass ADG as compared to those fed PIC2008 Lys curve (P< 0.05). There were NDF×Lys interactions (P< 0.10) for ADG, gain to feed ratio (G:F), carcass ADG, and carcass G:F. These response criteria were improved for pigs fed PIC2016 Lys curve compared to those fed PIC2008 Lys curve when NDF level was 13%; while no evidence of differences was observed at 20% NDF. Results indicate that increasing NDF level from 13 to 20% deteriorate performance of 30- to 130- kg pigs; and the improved growth performance of pigs fed PIC2016 Lys curve as compared to those fed PIC2008 Lys curve was only observed when lower NDF level was presented.